Genetic analysis of the NZB contribution to lupus-like autoimmune disease in (NZB x NZW)F1 mice. - Drake, C G (1994)
Lupus-like autoimmunity in (NZB x NZW)F1 mice is frequently marked by the development of a severe and fatal renal disease. Genes from both NZB and NZW parents are required for the full expression of disease. We applied a mapping technique based on polymorphism in simple sequence repeats to the analysis of (NZB x NZW)F1 x NZW backcross mice to determine the NZB genetic contribution to disease. The results show that a single NZB locus or tightly linked group of loci on the distal part of chromosome 4 provides the strongest association with renal disease and death. This locus, designated here as nba-1 (New Zealand Black autoimmunity), lies distal to the locus elp-1, 60-70 centimorgans from the centromere. It is of interest that a gene encoding a receptor for tumor necrosis factor maps to the vicinity of this disease-associated gene.